AB0253 A REVIEW OF SMOKING CESSATION STRATEGIES AND LUNG CANCER SCREENING PRACTICES IN PATIENTS WITH RHEUMATOID ARTHRITIS. (2nd June 2020) - Lopez-Olivo, M. A.; Volk, R.; Krause, K. J.; Suarez-Almazor, M.
Abstract : Background: Smoking rates among patients with rheumatoid arthritis (RA) exceed those reported in the general population. In addition, people with RA who smoke are more likely to develop lung cancer than smokers who do not have RA. Objectives: To identify smoking cessation strategies and lung cancer screening practices in patients with RA. Methods: We conducted a review of the literature in electronic databases (i.e., PubMed, EMBASE, Cochrane, Scopus, and Web of Science) from inception until June 2019. We included studies that reported on the results of interventions for smoking cessation or lung cancer screening in patients with RA. We excluded case reports, reviews, guidelines, protocols, or studies on tobacco use not reporting interventions. We included studies published in abstract or full-text format. We extracted study and intervention characteristics including delivery format, timing and results. Results: We retrieved 394 relevant citations and ultimately included 9 studies evaluating smoking cessation strategies, and one regarding lung cancer screening practices. Five studies were reported in abstract format. There were 3 studies conducted in the United Kingdom, and one each in Croatia, France, Ireland, New Zealand, Sweden, Spain and United States. Two studies were randomized control trials and the remaining were uncontrolled. Follow-up ranged between 1 month and 24 months, however, one study only reported data on the assessment immediately after the intervention. Sample sizes ranged between 20 and 185 current smokers. Smoking cessation strategies included: 1) brief advice and nicotine replacement therapy + smoking cessation counseling for 3 months; 2) information booklet on harms of smoking (i.e., impact on disease and treatment); 3) spoken information on harms of smoking (i.e., impact on disease and treatment) plus advice to quit smoking; 4) advice to quit smoking plus nicotine replacement; 5) smoking cessation support with contact every 4 weeks; 6) spoken information on harms of smoking (i.e., impact on disease and treatment) plus advice to quit smoking plus nurse telephone visit at 3 rd month; 6) staff driven tobacco QUIT line referral process; 7) multi-modality intervention with advise to quit smoking plus guidance on safe alcohol use plus dietary advise with booklet and swimming group. The lung cancer screening study reported on a program with nurse evaluation of comorbidities and risk factors, and recommendations for lung cancer screening with a chest X-ray and smoking cessation. Most studies reported benefits when implementing a structured plan to educate, counsel, and offer pharmacological treatment to patients with RA. Conclusion: There was large heterogeneity among studies in patient characteristics and interventions proposed, and outcomes. Only 2 studies were randomized clinical trials. Additional controlled studies are needed to determine best practices for smoking cessation and lung cancer screening in patients with RA. Disclosure of Interests: None declared